Uncertainty and Environmental Decision Making A Handbook of Research and Best Practice - Filar, Jerzy A.; Haurie, Alain; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Uncertainty and Environmental Decision Making: A Handbook of Research and Best Practice presents the state of the art in applying operations research and management science (OR/MS) techniques to a broad range of environmental decision making (EDM) challenges. Drawing on leading researchers in the field, it provides a guided tour of selected methods and tools to help deal with issues as climate change, depleting biodiversity and biocapacity, and more general atmospheric, water and soil pollution problems. Individual peer-reviewed chapters look at applying stochastic reasoning on difficult issues arising in EDM under uncertainty; applying stochastic or robust programming methods to techno-economic modeling of energy/environment interactions; important consequences of uncertainty inherent in weather patterns, the El Nino phenomenon and anticipated climate change; exploiting tools of decision analysis, utility theory and optimal control theory to account for differences in time scales between human development processes and the natural processes of the biosphere; and methods that combine statistical and decision analyses that can support a variety of environmental management problems. This important new work will be of special interest to a wide range of researchers, students, and practitioners in environmental economics, OR/MS, environmental and earth sciences, climatologists, and risk assessment.
OR/MS and Environmental Decision Making under Uncertainty -- Modeling Uncertainty in a Large scale integrated Energy-Climate Model -- Robust Optimization for Environmental and Energy Planning -- Coping with Climate Risks in Indonesian Rice Agriculture: A Policy Perspective -- A Primer on Weather Derivatives -- Optimal Control Models and Elicitation of Attitudes towards Climate Damages -- A Stochastic Control/Game Approach to the Optimal Timing of Climate Policies -- Precautionary Effect and Variations of the Value of Information -- Comparative Forecasting and a Test for Persistence in the El Niño Southern Oscillation -- Generation of Synthetic Sequences of Electricity Demand with Applications -- Models for Improving Management of Biosolids Odors.
Keywords: Environmental sciences; Environmental management; Regional economics; Environmental economics; Environment; Environmental Monitoring/Analysis.; Operations Research/Decision Theory; Math. Appl. in Environmental Science; Environmental Management; Regional/Spatial Science; Environmental Economics